A construção dos discursos que circulam entre a Ciência, a Tecnologia e a Sociedade no gênero “revista de atualidades” - Pugliese, Allan Tadeu (Universidade Federal de São Carlos, 2018)
The purposes of this study is to show how the translation of texts from the spheres of Science and Technology to more common spheres of the Society happens. For that we analyze the Brazilians magazines Superinteressante, Saúde e Vital, Quatro Rodas and Architecture & Construction - the four magazines publications of the publisher Abril. Our methodology was the collating of texts (GERALDI, 2012) and we went through the theories of the discursive genres (BAKHTIN, 2003), the design (DONDIS, 2007; SUDJIC, 2010) and the literary translation (PETRILLI, 2011; PONZIO, 2008) the translation with dialogic vision between languages and discursive spheres. The separation of these magazines was also created as "current news magazines". We can see how the translation occurs and that the various fields cited can help to build a new understanding of how to pass information to other discursive spheres.
The construction of the speeches that circulate between Science, Technology and Society in the genre "news magazine".
Keywords: Discurso; Ciência, Tecnologia e Sociedade; Tradução; Design; Bakhtin, Mikhail Mikhailovitch, 1895-1975; Speeches; Science, Tecnology e Society; Translation; LINGUISTICA, LETRAS E ARTES::ARTES